Effects of catalase, 2% chlorhexidine gel and 1% sodium hypochlorite on the microtensile bond strength of teeth bleached with 35% hydrogen peroxide - Ricardo Ferreira; Tassiana Vieira Nunes; Betsy Kilian Martins Luiz; Rubens Nazareno Garcia (Revista Sul-Brasileira de Odontologia, 2012)
Introduction and objective: Dental bleaching is an effective, relatively simple and noninvasive technique. The aim of this study was to evaluate the effects of catalase, 2% chlorhexidine gel, and 1% sodium hypochlorite on the microtensile bond strength to enamel of bovine teeth submitted to internal and external bleaching with 35% hydrogen peroxide. Material and methods: Sixty bovine incisors were used. They had their debris removed, washed in tap water and stored frozen. The samples were divided into five experimental groups according to the treatment applied after bleaching (n = 12): 1 − control/no bleaching (C); 2 − catalase (CA); 3 − 2% chlorhexidine gel (CG); 4 − 1% sodium hypochlorite (SH); 5 − distilled water (DW). For microtensile test, samples were prepared into blocks of enamel/resin, which were sectioned to obtain hourglass-like specimens. Bond strength was calculated in MPa and data analyzed statistically by Anova (p < 0.05). Results: Microtensile bond strength means decreased in comparison to control group, but no statistically significant difference between groups was found. Conclusion: The substances used after dental bleaching did not result in statistically significant microtensile bond strength means of the tested groups.